(untitled) (Journal of Engineering, 2024)
Land use is the human modification of the natural or terrestrial environment into a built environment such as fields, pastures, and settlements. Baghdad, like most cities in the world, suffers from many urban problems, especially the problems associated with the disparity in the distribution of land uses and deficiencies in their distribution according to scientific standards and foundations, such as the problem of pollution and overpopulation. Karrada was chosen because it represents a large urban center in Baghdad, with about 1 million people spread over about 72 km2. The aim is to assess land use in Karrada. In addition to the analysis of land uses in the study area, and the study of changes that occurred in those uses, either the study methodology has adopted the descriptive and analytical approach based on the data and information obtained from the municipality of Karrada. Comparison was used as a method of evaluation and geographic information systems (GIS) technology was used to achieve the set objectives. The research lasted almost a year, and the study found that the land uses in Karrada are far from what they were designed for and from planning standards, as it was found that agricultural use decreased significantly, and its lands turned into other uses such as residential and institutional use. Creating land use maps for the years 1973 and 2022 was one of the most important results of this study in conclusion, the study called for several recommendations Among them is the need to adhere to planning standards for land uses to achieve spatial justice in the distribution of those uses and to benefit from the experiences of countries in the field of land and investment promotion.